Effect of Physical Exercise on the Febrigenic Signaling is Modulated by Preoptic Hydrogen Sulfide Production. - Jonatas E Nogueira; Renato N Soriano; Rodrigo A R Fernandez; Heloísa D C Francescato; Rafael S Saia; Terezila M Coimbra; José Antunes-Rodrigues; Luiz G S Branco (PLoS ONE, 2017)
We tested the hypothesis that the neuromodulator hydrogen sulfide (H2S) in the preoptic area (POA) of the hypothalamus modulates the febrigenic signaling differently in sedentary and trained rats. Besides H2S production rate and protein expressions of H2S-related synthases cystathionine β-synthase (CBS), 3-mercaptopyruvate sulfurtransferase (3-MPST) and cystathionine γ-lyase (CSE) in the POA, we also measured deep body temperature (Tb), circulating plasma levels of cytokines and corticosterone in an animal model of systemic inflammation. Rats run on a treadmill before receiving an intraperitoneal injection of lipopolysaccharide (LPS, 100 μg/kg) or saline. The magnitude of changes of Tb during the LPS-induced fever was found to be similar between sedentary and trained rats. In sedentary rats, H2S production was not affected by LPS. Conversely, in trained rats LPS caused a sharp increase in H2S production rate that was accompanied by an increased CBS expression profile, whereas 3-MPST and CSE expressions were kept relatively constant. Sedentary rats showed a significant LPS-induced release of cytokines (IL-1β, IL-6, and TNF-α) which was virtually abolished in the trained animals. Correlation between POA H2S and IL-6 as well as TNF-α was observed. Corticosterone levels were augmented after LPS injection in both groups. We found correlations between H2S and corticosterone, and corticosterone and IL-1β. These data are consistent with the notion that the responses to systemic inflammation are tightly regulated through adjustments in POA H2S production which may play an anti-inflammatory role downmodulating plasma cytokines levels and upregulating corticosterone release.